n - 1
t(n) = n(n - 3)
The Nth term in the series is [ 2N ] .
They are: nth term = 6n-4 and the 14th term is 80
If you mean: 2 4 8 16 32 64 it is 2^nth term and so the next number is 128
n - 1
If the nth term is 8 -2n then the 1st four terms are 6, 4, 2, 0 and -32 is the 20th term number
t(n) = n(n - 3)
The nth term is (2n - 12).
(n2+n+2) / 2, starting with n=0.
The Nth term in the series is [ 2N ] .
They are: nth term = 6n-4 and the 14th term is 80
If you mean: 3, 4, 5, 6 and 7 then nth term = n+2
11
16 - 4nor4 (4 - n)
If you mean: 2 4 8 16 32 64 it is 2^nth term and so the next number is 128
The given sequence appears to be increasing by 10 each time. To find the nth term, we can use the formula for arithmetic sequences: nth term = first term + (n-1) * common difference. In this case, the first term is 4 and the common difference is 10. Therefore, the nth term for this sequence would be 4 + (n-1) * 10, which simplifies to 10n - 6.